2022
DOI: 10.1002/hep4.1923
|View full text |Cite
|
Sign up to set email alerts
|

Global and regional long‐term survival following resection for HCC in the recent decade: A meta‐analysis of 110 studies

Abstract: Surgical resection for HCC remains a major curative treatment option, but it is unclear whether there are differences in outcomes by region and whether outcomes have improved over time. We aimed to estimate pooled overall survival (OS), recurrence‐free survival (RFS), and complication rates in patients with hepatocellular carcinoma (HCC) following curative surgical resection and to compare outcomes by region and by time period. In this systematic review and meta‐analysis, we searched Pubmed, Embase, and Cochra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 40 publications
1
31
0
Order By: Relevance
“…According to the world health organization GLOBOCAN database, HCC is rapidly becoming the leading cause of cancer deaths in the United States and is the fourth leading cause of cancer-related deaths worldwide. The tumor prognosis remains poor with a five-year survival rate of around 18% [ 8 ]. In the United States, the annual incidence of HCC is 6 per 100,000 [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to the world health organization GLOBOCAN database, HCC is rapidly becoming the leading cause of cancer deaths in the United States and is the fourth leading cause of cancer-related deaths worldwide. The tumor prognosis remains poor with a five-year survival rate of around 18% [ 8 ]. In the United States, the annual incidence of HCC is 6 per 100,000 [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite surveillance programs, the majority of patients with HCC are diagnosed at an advanced stage [ 3 - 7 ]. Overall, the prognosis of HCC is poor, even among patients who have undergone curative treatment [ 8 - 11 ]. Studies have demonstrated poor quality of life (QOL) among patients with HCC due to complications of the cancer and decompensated liver cirrhosis including pruritus, fatigue, sexual dysfunction, and ascites [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hepatocellular carcinoma (HCC) is the third leading cause of cancer-related death worldwide [ 1 , 2 ]. The optimal treatment for HCC is oncologic resection or liver transplant [ 3 , 4 , 5 , 6 ]. Unfortunately, this is often limited by poor liver function precluding a safe resection and a shortage of donor livers.…”
Section: Introductionmentioning
confidence: 99%